2014
DOI: 10.5367/oa.2014.0156
|View full text |Cite
|
Sign up to set email alerts
|

Waterproofing Wheat — A Re-Evaluation of Film Antitranspirants in the Context of Reproductive Drought Physiology

Abstract: Film antitranspirants are polymers sprayed on plants to reduce loss of water from transpiration. Early reviews of film antitranspirants logically concluded that the polymers would not be useful on crops because photosynthesis was also reduced. This conclusion is re-evaluated here, taking account of more recent knowledge of drought damage mechanisms. Research at Harper Adams University shows that film antitranspirants applied to wheat before the drought-sensitive stage of meiosis can increase yield, despite red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…A broader approach has been suggested, since photosynthesis and yield not only depend on crop physiology but also on the interaction with crop developmental stages (Kettlewell, 2014;Kettlewell et al, 2010) and ambient CO 2 levels (del Amor et al, 2010). Wheat is most sensitive to drought during booting, which coincides with meiosis of pollen mother cells (Saini and Westgate, 1999;Sheoran and Saini, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…A broader approach has been suggested, since photosynthesis and yield not only depend on crop physiology but also on the interaction with crop developmental stages (Kettlewell, 2014;Kettlewell et al, 2010) and ambient CO 2 levels (del Amor et al, 2010). Wheat is most sensitive to drought during booting, which coincides with meiosis of pollen mother cells (Saini and Westgate, 1999;Sheoran and Saini, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to optimize water use efficiency by reducing water loss while sustaining the yield under drought conditions (AbdAllah et al, 2018). Film antitranspirants (AT) are emulsions sprayed on the surface of leaves that create a waterproof layer to block stomata and thereby decreasing the diffusion of water vapor (Gale and Poljakoff-Mayber, 1967;Kettlewell, 2014;Abdullah et al, 2015). The reduction of water loss from AT application is usually accompanied by the limitation on photosynthesis due to the low permeability of films to CO 2 entering the leaf, accordingly, film AT are mainly applied on ornamental species, in which photosynthesis is less important than the reduction of transpiration (Das and Raghavendra, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a comprehensive study by showed that AT should target the most drought sensitive stage to avoid counterproductive effects. The potential of ATs to 'waterproof' the most critical crop development stages (Kettlewell, 2014) through reduced transpiration and improve water use efficiency (WUE) during drought is an active area of research.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is important to note that photosynthesis is partially reduced and not completely stopped by ATs, and that the reduction in carbon assimilation is outweighed by the benefit if the products are applied to protect the most drought sensitive stage (Kettlewell, 2014). Das and Raghavendra (1979) concluded that AT products were only economically feasible for specific enterprises such as high value fruit production.…”
Section: Introductionmentioning
confidence: 99%